2018
DOI: 10.1161/atvbaha.117.310626
|View full text |Cite
|
Sign up to set email alerts
|

IL-35 (Interleukin-35) Suppresses Endothelial Cell Activation by Inhibiting Mitochondrial Reactive Oxygen Species-Mediated Site-Specific Acetylation of H3K14 (Histone 3 Lysine 14)

Abstract: IL-35 is induced during atherosclerosis development and inhibits mitochondrial reactive oxygen species-H3K14 acetylation-AP-1-mediated EC activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
104
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(109 citation statements)
references
References 58 publications
5
104
0
Order By: Relevance
“…Contrary to clinical experiments, as an anti-inflammatory cytokine, IL-35 expression in mouse atherosclerotic plaques was significantly increased . A small number of other studies, however, have reported increased IL-35 expression in atherosclerotic plaques and serum in ApoE mice fed with a high-fat diet, as well as in the plasma of patients with coronary artery disease (Gorzelak-Pabiś et al, 2017;Li et al, 2018). Using a mouse model of atherosclerosis, administration of recombinant mouse IL-35 significantly decreased plaque area in the aortic root, and Treg immune responses were also found to be enhanced (Tao et al, 2016).…”
Section: Animal Studiesmentioning
confidence: 94%
See 1 more Smart Citation
“…Contrary to clinical experiments, as an anti-inflammatory cytokine, IL-35 expression in mouse atherosclerotic plaques was significantly increased . A small number of other studies, however, have reported increased IL-35 expression in atherosclerotic plaques and serum in ApoE mice fed with a high-fat diet, as well as in the plasma of patients with coronary artery disease (Gorzelak-Pabiś et al, 2017;Li et al, 2018). Using a mouse model of atherosclerosis, administration of recombinant mouse IL-35 significantly decreased plaque area in the aortic root, and Treg immune responses were also found to be enhanced (Tao et al, 2016).…”
Section: Animal Studiesmentioning
confidence: 94%
“…81760051 to YL). Lee et al, 1999;Davenport and Tipping, 2003;Hauer et al, 2005;Koltsova et al, 2012;Hirase et al, 2013;Wang et al, 2014;Subramanian et al, 2015;Tao et al, 2016;Gorzelak-Pabiś et al, 2017;Engelbertsen et al, 2018;Fatkhullina et al, 2018;Li et al, 2018;Ryu et al, 2018;Huang et al, 2019;Wang et al, 2019…”
Section: Fundingmentioning
confidence: 99%
“…IL-35 has been identified as a functional cytokine of regulatory T cells. IL-35 plays an anti-inflammatory role and ameliorates atherosclerosis [ 15 ], autoimmune disease [ 16 ], autoimmune diabetes [ 17 ], arthritis [ 18 , 19 ], and explosive hepatitis [ 20 ]. The biological effects of IL-12 and IL-35 were abrogated when the IL-12p35 subunit was knocked out.…”
Section: Introductionmentioning
confidence: 99%
“…IL-35 protected against acute liver and kidney injury caused by LPS through inhibiting inflammatory responses (27,28). IL-35 also inhibited lysophosphatidylcholine-induced mitochondrial reactive oxygen species (mtROS) production and human aortic endothelial activation (29,30). Furthermore, IL-35 was reported to exert anti-apoptotic effects that prevent diabetic neuropathic pain and doxorubicin-induced cardiac injury (24,31).…”
Section: Discussionmentioning
confidence: 99%